AUTOMATED BIOLECTRICAL GARDEN FOR SUSTAINABLE ENERGY GENERATION IN THE EL CHORRO ANNEX - Silva Abanto, Roger; Briones, Yanet; Escobar, Mayra; Limay, Jenny; Mendoza, Juan; Ramírez, Brestley; Vásquez, Fredin (LACCEI, 2025)
Abstract– The objective of this project was to develop and implement an Automated Bioelectric Garden as a sustainable alternative for generating electricity in rural areas without access to conventional service, focusing on the El Chorro Annex, La Libertad de Pallán district, Cajamarca. The methodology consisted of designing and assembling microbial fuel cells using live succulent plants, zinc and copper electrodes, and silt loam soil, without including energy storage systems. The cells were connected in series and parallel to directly power a 3W LED bulb. Experimental results showed that each plant generated an average of 0.4 volts, which was insufficient to power the bulb; at least six connected plants were required to reach the necessary voltage. Despite not achieving direct ignition, the technical feasibility of the bioelectric principle and the structural functionality of the system were validated. It is concluded that this technology represents an environmentally friendly, low-cost, and replicable solution, but requires improvements in system architecture, preferential use of zinc as an anode, the incorporation of electrical storage, and community training strategies for its effective and sustainable implementation in vulnerable rural areas.